Supercritical Fluid Extraction of Quinones from Compost for Microbial Community Analysis - Ni Luh Gede Ratna Juliasih; Lee Chang Yuan; Yuki Sago; Yoichi Atsuta; Hiroyuki Daimon (Journal of Chemistry)
Supercritical fluid extraction (SFE) was used to extract quinones from compost to monitor the microbial community dynamics during composting. The 0.3 g of dried compost was extracted using 3 mL min−1 of carbon dioxide (90%) and methanol (10%) at 45°C and 25 MPa for a 30 min extraction time. The extracted quinones were analysed using ultra performance liquid chromatography (UPLC) with 0.3 mL min−1 of methanol mobile phase for a 50 min chromatographic run time. A comparable detected amount of quinones was obtained using the developed method and an organic solvent extraction method, being 36.06 μmol kg−1 and 34.54 μmol kg−1, respectively. Significantly low value of dissimilarity index (D) between the two methods (0.05) indicated that the quinone profile obtained by both methods was considered identical. The developed method was then applied to determine the maturity of the compost by monitoring the change of quinone during composting. The UQ-9 and MK-7 were predominant quinones in the initial stage of composting. The diversity of quinone became more complex during the cooling and maturation stages. This study showed that SFE had successfully extracted quinones from a complex matrix with simplification and rapidity of the analysis that is beneficial for routine analysis.